Avaliação de variedades locais de milho em sistema de plantio direto orgânico sob dois manejos de palha - Barreto, Guilherme Bortolini (2020)
Fundamental in the world production scene, the corn has importance and prominence in various countries of the world, being also recognized for having varieties endowed with rusticity and genetic variability, essential for plant-growing programs, because of the alleles used for the cultivated varieties, and for family farming, for give sustainability and low costs of agricultural crops. With wide geographic adaptability, the local varieties of creole maize have been tested in no medium plan, more precisely in the municipalities of Passo Fundo and Carazinho, being able to express their phenotypic characteristics in organic farming systems with the use of no-tillage. This discussion was organized in two chapters, as a first study conducted by the Agricultural Research Center of the Passo Fundo University, on a conventional hybrid (22s18 - Semper Sementes) and the landraces "Franco-brasileiro", "Aztequinha", "Cabo roxo ” being cultivated in agricultural year of 2018/19, on an interruption of cover crops with a roller-crimper of 2.4m weighted with water, favoring a “ mulch ”necessary for no-tillage, managing spontaneous plants and guaranteeing the soil conservation . The experimental delineation was blocks to perhaps, with 5 repetitions, and the space used foi 0.45 m between fillets and 0.3 m between plants. Excellent produtivities of the conventional hybrid (9042.47 kg ha-1) were observed and there were 12 species of spontaneous plants that emerged from mulch. The cycle on days two materials does not appear significantly different, just "Cabo roxo" differed significantly of other genotypes in plant height at the end of the cycle (209.9 cm). Among the characteristics of spike, in the weight of grains per spike, the conventional hybrid reaches 170.4 g, differing of the other treatments. It was verified that there was little significant difference between the landraces and the conventional hybrid in an organic production system with the use of mulch. In a second study, conducted in the experimental area of the Escola Estadual de Educação Profissional de Carazinho, the landraces "Oito carreiro", "Brancão", "Ferro", "Palha de seda", "Palha roxa", "Cabo roxo" and “Dente de ouro” and the same hybrid of the first test of the discussion, was tested in an experiment with the delineation of blocks randomizes with a bifatorial scheme (8x2), with two handles of mulch, cutting and interruption with the roller crimper. This experiment was conducted in the 2019/20 agricultural year. The yeld of landraces surprising, in an agricultural year characterized by water deficit of 280 mm in relation to historical data years. The landrace “Brancão”, with a performance of 11 938.08 kg ha-1, in the cutting manage, significantly different of other genotypes tested, and 18 species of spontaneous plants emerged in the experimental area, on the mulch managements used, in this study. The organic system conditions or the cycle of the tested genotypes, whereas the conventional hybrid, generally considered precocious in proper cultivation conditions, differing of the other treatments showing it to be or more late.